2019
DOI: 10.1007/s11156-019-00797-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risk-shifting in U.S. commercial banking

Abstract: This paper puts forward the proposition that U.S. commercial banks use dividends as a mechanism to shift systemic risk to debt-holders and the deposit insurer. Using a mixed data sampling modeling approach, it is shown that monthly systemic risk factors are associated with a positive effect on future quarterly bank dividends indicating systemic risk-shifting. These factors include absorption (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For instance, (Acharya et al 2017) introduces a measurement based on the systemic expected shortfall (SES). Recently (Kanas and Zervopoulos 2020) and (Lin et al 2018) examined in total 8 risk factors including SRISK, absorption (Kritzman et al 2011), CATFIN (Allen et al 2012), MES (Acharya et al 2011), Co-VaR (Adrian andBrunnermeier 2011), ∆CoVaR (Adrian and Brunnermeier 2011), real_vol (Giglio et al 2016), and size_con (Giglio et al 2016). The accuracy tests suggested that there are very marginal differences across the competing systemic risk factors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For instance, (Acharya et al 2017) introduces a measurement based on the systemic expected shortfall (SES). Recently (Kanas and Zervopoulos 2020) and (Lin et al 2018) examined in total 8 risk factors including SRISK, absorption (Kritzman et al 2011), CATFIN (Allen et al 2012), MES (Acharya et al 2011), Co-VaR (Adrian andBrunnermeier 2011), ∆CoVaR (Adrian and Brunnermeier 2011), real_vol (Giglio et al 2016), and size_con (Giglio et al 2016). The accuracy tests suggested that there are very marginal differences across the competing systemic risk factors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Higher NPL rates reflect riskier lending practices (Nakano and Nguyen 2012). BHC Tail Risk (Ellul and Yerramilli 2013;Kanas and Zervopoulos 2019) is the negative of the average return on the BHC's stock over the 5% worst return days annually. BHCs with an independent and effective risk management function should have lower enterprise-wide tail risk (Kashyap et al 2008).…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Tail Risk is closely related to the Marginal Expected Shortfall Measure (MES) used elsewhere in the literature to proxy the propensity to experience a capital shortfall in stress conditions (Acharya et al 2011;Iqbal and Vähämaa 2018). (Kanas and Zervopoulos 2019) describe this measure as a systemic fragility metric. Capital ratios are an important predictor of bank risk (Hogan et al 2017).…”
Section: Dependent Variablesmentioning
confidence: 99%